An Empirical Model for Assessing the Impact of Air Quality on Urban Residents' Loyalty to Place of Residence. (September 2021) - Karaca, Ferhat; Turkyilmaz, Ali; Myrzagali, Alikhan; Kerimray, Aiymgul; Bell, Phillip
There has been a growing interest in the impact of environmental awareness on 'green' or 'environmentally friendly' consumption patterns, and this has been the subject of much research by environmental psychologists. However, the effect of environmental awareness on residents and their attachment to their homes and their environment has received little attention and is worthy of closer examination. Outdoor air quality can be considered one of the most critical environmental factors impacting the value of a residential location. This research investigates how air pollution-related environmental factors influence residents' attachment to the place of residence and their willingness to move. It defines the structural relationship between air pollution awareness parameters, which are later employed in the proposed structural equation model (SEM), to explain 'district loyalty'. A survey was carried out in Almaty, Kazakhstan, one of the most populated and polluted cities in Central Asia. A total of 550 respondents responded. Based on the overall model's test results, the factors relating to district loyalty explained the 17.5% variation in the samples, which suggests that the perception of residents to their district air quality has a low-level impact on loyalty to their place of residence. The power of perceived environmental risks appears to have little relation to district loyalty. The most influential factor on the model is environmental behaviour parameter, which is about adopting attitudes and behaviours aimed at minimizing negative impacts on the environment. When the perceived environmental risk increased, their place attachment levels only slightly decreased. However, the obtained results do not confirm that district loyalty significantly correlates with their readiness/unreadiness to move to another residence in order to enjoy improved air quality. To sum up, environmental awareness of local air quality seems not to directly affect residents' attachment to place. Nevertheless, indirect effects can be presented in research relating to urban residents' place attachment. Research, policy and sectoral implications of the findings are addressed and discussed in detail.